Histological evaluation of the early bone response to hydroxyapatite (HA) implanted in rabbit tibia - Khalid, Khadijah; Masri, Mashita; Saidu, Mohd Fharid; Fazan, Fazilah; Khalid, Kamarul Ariffin (2004)
This study is to qualitatively evaluate a locally produced hydroxyapatite (HA), made by AMREC-SIRIM in an experimental animal bone defect using New Zealand White (NZW) rabbits. HA cylindrical blocks measuring 2.5 mm (D) x 1.0 mm (H) were implanted in the rabbits' left tibia. The tibias were harvested within one to three weeks post-implantation. The implantion site was cut into thin undecalcified sections of about 30 microm to 60 microm and stained with Toluidine Blue and Goldner's Masson Trichrome. Microscopic examinations using standard light microscopy of these slides were performed.